Persepsi terhadap budaya kualiti dalam organisasi perkhidmatan awam - Ismail, Khazani (2006)
This study focuses on the perception of quality culture in the organisation of public services. Several factors were identified to have influenced the quality culture in such organisations. As such, the objectives of this study are to (1) identify the level of importance of the main factors that contributes to quality culture practices and (2) identify the level of aplication of the main factors that contributes to quality culture practices. The study was carried out by using questionnaire survey to collect the relevant information. The staffs of Valuation and Property Services Department, State of Pahang were taken as respondents for this study. The collected data were analysed by using descriptive statistic technique which are frequency, percentage and comparable mean. Independent-Sample t-Test analysis and ANOVA were also applied to identify whether the difference in variable mean were statistically significant or not. The result of this study has identified that the most important factors that contribute to the practises of quality culture were motivation and organisation structure. The other two factors; personal involvement and recognition were less important. The rest of five factors; empowerment, leadership, communication, teamwork, and education and training were the least important. The level of application of the factors were relatively low as compared with the level of importance. The level of importance for education and training factor only was significantly different based on respondent’s background. Besides that, the genders, types of services and the ages of the respondents made a significant difference in the level of application of those factors